Key Process Indicators of Mortality in the Implementation of Protocol-driven Therapy for Severe Sepsis - Jiun-Long Wang; Chun-Shih Chin; Ming-Chen Chang; Chi-Yuan Yi; Sou-Jen Shih; Jeng-Yuan Hsu; Chieh-Liang Wu (Journal of the Formosan Medical Association, 2009)
Severe sepsis and septic shock are life-threatening disorders. Integrating treatments into a bundle strategy has been proposed to facilitate timely resuscitation, but is difficult to implement. We implemented protocol-driven therapy for severe sepsis, and analyzed retrospectively the key process indicators of mortality in managing sepsis. Methods: Continuous quality improvement was begun to implement a tailored protocol-driven therapy for sepsis in a 24-bed respiratory intensive care unit (RICU) of Taichung Veterans General Hospital from January 2007 to February 2008. Patients, who were admitted to the RICU directly, or within 24 hours, were enrolled if they met the criteria for severe sepsis and septic shock. Disease severity [Acute Physiology and Chronic Health Evaluation (APACHE) II and lactate level], causes of sepsis, comorbidity and site of sepsis onset were recorded. Process-of-care indicators included resuscitation time (Tr-s), RICU bed availability (Ti-s) and the ratio of completing the elements of the protocol at 1, 2, 4 and 6 hours. The structure and process-of-care indicators related to mortality at 7 days after RICU admission and at RICU discharge were identified retrospectively. Results: Eighty-six patients (mean age, 71 ± 14 years; 72 men, 14 women; APACHE II, 25.0 ± 7.0) were enrolled. APACHE II scores and lactate levels were higher for mortality than survival at 7 days after RICU admission (p < 0.01). For the process-of-care indicators, Ti-s (562.2 ± 483.3 vs.1017.3 ± 557.8 minutes, p = 0.03) and Tr-s (60.7 ± 207.8 vs. 248.5 ± 453.1 minutes, p = 0.07) were shorter for survival than mortality at 7 days after RICU admission. The logistic regression study showed that Tr-s was an important indicator. The ratio of completing the elements of protocols at 1, 2, 4 and 6 hours ranged from 70% to 90% and was not related to mortality. Conclusion: Protocol-driven therapy for sepsis was put into clinical practice. Early resuscitation and ICU bed availability were key process indicators in managing sepsis, to reduce mortality.